A qualitative study of school leader experiences adopting and implementing a whole of school physical activity and sedentary behaviour programme: Transform-Us!. Issue 3 (26th October 2020) - Cassar, Samuel; Salmon, Jo; Timperio, Anna; Koch, Sofie; Koorts, Harriet
Abstract : Purpose: Little is known about the experiences of school leaders adopting and implementing real-world, scaled-up physical activity interventions in the Australian educational system. Transform-Us! is a novel physical activity and sedentary behaviour intervention available to all primary schools in Victoria, Australia, since September 2018. This study explored barriers and facilitators experienced by school leaders during the adoption and early implementation phases of Transform-Us!. Design/methodology/approach: Qualitative study involving seven semi-structured telephone interviews with school leaders implementing Transform-Us! in primary schools in Victoria, Australia. Interview schedules were developed based on the theoretical domains framework (TDF). Interviews were coded using a framework analysis approach. Findings: Four key themes emerged relating to ten of the 14 TDF domains. Themes included: knowledge, goals, implementation factors and leadership. School leaders play a central role in creating a positive implementation environment including the delivery setting (classroom) and a supportive culture (knowledge sharing) in the school. The application of the TDF to the study bridges the gap between theory and practice and identifies potential future implementation strategies which may be further tested in professional practice future studies. Recommendations for increased adoption and sustained implementation related to seven core areas: presence of a school/programme champion(s); collaborative knowledge sharing; online training; school-based workshops; promotion of behavioural and mental health outcomes; teacher autonomy in delivery; and a supportive implementation environment. Originality/value: School leaders have a unique scope to influence the adoption and implementation of physical activity and sedentary behaviour interventions. This study outlines specific barriers and facilitators for implementation of a physical activity programme in the Australian educational setting and offers recommendations for programme optimisation.